Pastoral care in a trauma center - Landry, Victor L. (Journal of religion and health, 1996)
The pastoral staff of the Mercy Hospital of Pittsburgh, Pennsylvania, is a vital participant in the advanced trauma-care team. The staff of professionally certified chaplains take an active role in ministering to the unique temporal, psychological, and spiritual needs of both patients and patients' families. These professionals serve as hosts, counselors, confidants, and friends to people who have been suddenly thrown into chaos. The pastoral staff at a trauma center also ministers to the emotional and spiritual needs of the various medical and nursing staffs.